2021
DOI: 10.1007/s00204-021-03121-0
|View full text |Cite
|
Sign up to set email alerts
|

The application of cytokeratin-18 as a biomarker for drug-induced liver injury

Abstract: Drug-induced liver injury (DILI) is a frequent and dangerous adverse effect faced during preclinical and clinical drug therapy. DILI is a leading cause of candidate drug attrition, withdrawal and in clinic, is the primary cause of acute liver failure. Traditional diagnostic markers for DILI include alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP). Yet, these routinely used diagnostic markers have several noteworthy limitations, restricting their sensitivity, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 75 publications
(147 reference statements)
2
22
0
Order By: Relevance
“…In a study of obese children, linear regression showed that CK-18 was associated with WHR, FLI and adiponectin levels, which is consistent with the results of the correlation analysis in our study. Among other candidate markers studied (glutamate dehydrogenase, macrophage colony stimulating factor receptor and osteopontin), CK-18 is more sensitive and specific in diagnosing early-stage drug-induced liver injury and has a demonstrated strong relationship with hepatocellular injury in the clinic [ 37 ]. Recent studies also indicated the association of CK-18 with molecular markers of liver diseases, such as various types of microRNA, in particular miRNA-122 [ 36 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of obese children, linear regression showed that CK-18 was associated with WHR, FLI and adiponectin levels, which is consistent with the results of the correlation analysis in our study. Among other candidate markers studied (glutamate dehydrogenase, macrophage colony stimulating factor receptor and osteopontin), CK-18 is more sensitive and specific in diagnosing early-stage drug-induced liver injury and has a demonstrated strong relationship with hepatocellular injury in the clinic [ 37 ]. Recent studies also indicated the association of CK-18 with molecular markers of liver diseases, such as various types of microRNA, in particular miRNA-122 [ 36 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These values were higher than those reported in our study, which is consistent with the fact that participants involved in our study were obese but clinically healthy. Nevertheless, it is worth noting that CK-18 is released excessively from the liver into the circulation not only in NAFLD/NASH, but also in alcoholic liver disease (ALD), hepatitis B and hepatitis C patients and drug-induced liver injury [ 37 , 38 , 42 , 43 , 44 ]. Additionally, in acetaminophen-induced acute liver failure, serum CK-18 levels were associated with liver dysfunction and post-transplant graft failure, with levels > 900 U/L indicating 1-year graft loss [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its upregulation has been also suggested as a potential biomarker for hepatic injury. 37 Thus, any significant alterations in the levels of CK-18 over the culture days will indicate alteration in the normal levels of the hepatocytes and will indicate progression towards disease states. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that K18 and ccK18 are not liver-specific proteins and serum levels therefore rise with other organ conditions as well as with a variety of adenocarcinomas. 22 Despite this, K18 and ccK18 could be potentially useful for early DILI detection, particularly during drug development, based on the fact that serum elevations of cytokeratin-18, in particular uncleaved protein, appear earlier than ALT in acetaminophen-induced liver injury and consequently is more sensitive. 23 These candidate biomarkers can also provide mechanistic insights due to their reflection of necrotic and apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%